Effect of Macrocapsule Geometry on PCM Performance for Thermal Regulation in Buildings - Margarida Gonçalves; António Figueiredo; German Vela; Filipe Rebelo; Ricardo M. S. F. Almeida; Mónica S. A. Oliveira; Romeu Vicente (Energies)
The integration of phase-change materials (PCMs) into thermal energy storage systems offers significant potential for reducing energy consumption and improving thermal comfort, crucial issues for achieving sustainable building stocks. Nevertheless, the performance of PCM-based systems is strongly influenced by the container geometry. Among the various forms of incorporating PCMs into building applications, macroencapsulation is the most versatile and is, therefore, widely used. Herewith, this paper analyzes the impact of macrocapsule geometry on PCM thermal performance. Thermal properties of the material were first tested using Differential Scanning Calorimetry at five heating/cooling rates to evaluate its influence on phase-change temperatures and enthalpy. Then, an experimental setup evaluated four macrocapsule geometries on the enclosed PCM behavior during charging and discharging processes. The PCM characterization revealed that the slowest-tested rate minimized the supercooling effect. Analysis across different macrocapsule geometries showed that sectioning the contact surface improved heat transfer efficiency by fully mobilizing the PCM and reducing phase-change times. Conversely, double-layered geometry designs hindered heat transfer, presenting challenges in completing PCM charging and discharging. These findings suggest that optimizing its performance is a necessary direction for further research, which may include adjusting the PCM operating temperature range across layers or redesigning the geometry to misalign contact surfaces.